Pengaruh Model Pembelajaran Mind Mappping Terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri 091517 Hatonduhan - Intan Kandace Siallagan; Asister F Siagian; Andriono Manalu (JOURNAL SAINS STUDENT RESEARCH, 2023)
Thel relselarch ailms to deltelrmilnel: Thel ilnfluelncel of thel Milnd Mappilng Lelarnilng Modell on Scilelncel Lelarnilng Outcomels iln Class V of SD Nelgelril 091517 Hatonduhan T.A.2023/20224. Thel typel of relselarch useld iln thils relselarch ils Quantiltatilvel relselarch, whilch statels that quantiltatilvel relselarch ils relselarch iln thel form of numbelrs and Thel analysils usels statilstilcs. Thel relselarch delsilgn useld ils an elxpelrilmelnt, wilth thel form of Prel-Elxpelrilmelntal Delsilgn whilch usels thel "Onel group preltelst posttelst delsilgn" delsilgn. Thel samplel iln thils study was thel filfth gradel studelnts of SD Nelgelril 091517 Hatonduhan, totalilng 20 studelnts, of whilch thelrel welrel 10 malel studelnts and 10 felmalel studelnts. Thel ilnstrumelnt useld iln thils relselarch was a telst. Thel relsults of telstilng thel relselarch hypothelsils welrel that thelrel was an ilnfluelncel that silgnilfilcant iln thils relselarch from thel data that has beleln telsteld thel data can bel seleln from thel data analysils that thel avelragel relsults obtailneld iln thel Preltelst arel 49.75 and thel Posttelst ils 86.25. Thel relselarch relsults arel at thel 0.05 lelvell. Baseld on data analysils thel preltelst and posttelst valuels show that thel valuels arel silgnilfilcant .So ilt can bel concludeld that thelrel ils a silgnilfilcant ilnfluelncel on ilmprovilng thel lelarnilng outcomels of studelnts who usel thel Milnd Mappilng lelarnilng modell on ilmprovilng thel lelarnilng outcomels of class V studelnts at SD Nelgelril 091517 Hatonduhan for thel 2023/2024 acadelmilc yelar.